EKSPLORASI ANIMASI ADIT SOPO JARWO SEBAGAI MEDIA GAME BASED LEARNING DALAM PENGUATAN KARAKTER SISWA SEKOLAH DASAR - Dawamur Rozaq; Hitta Alfi Muhimmah; Nurul Inayah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the urgency of strengthening character education for elementary school students amidst various challenges in today's children's behavioral development, such as a lack of discipline, responsibility, and cooperation. Furthermore, this research stems from a school program that encourages students to watch animated films as a medium for learning life values. The purpose of this study is to explore the potential of the animated film Adit Sopo Jarwo, integrated with game-based learning, in developing the character of third-grade elementary school students. The research results show that animated films can foster students' initial understanding of the values ​​of honesty, responsibility, cooperation, hard work, and perseverance. The integration of game-based learning activities makes students more active, enthusiastic, and engaged in the learning process. However, behavioral changes do not occur instantly because there is still a gap between students' understanding and actual practice. The study's conclusions indicate that film-based and game-based learning have strong potential for developing student character. However, their effectiveness is influenced by the duration and variety of media, the role of the teacher, and the support of the school environment. Therefore, implementation needs to be sustainable and contextualized to ensure optimal character development in students.